A Mediaeval Persian Treatise on Coloured and Enamelled Glass: Bayan Al-Sana'at. Issue 2 (1st January 2016) - Holakooei, Parviz
Abstract: This paper presents and interprets the terms and concepts described by Hobaysh Teflisi in the twelfth century AD for making Islamic coloured and enamelled glass and lustre decorations. These descriptions comprise the fourth and fifth chapters of Bayan al-Sana'at, a book for "explaining crafts". The instructions contained in these chapters can be considered as one of the first references on glass making and enamelling on glass in Persian literature. Although the recipes suggested by Teflisi demonstrate fairly accurate methods, materials and techniques, they are sometimes misleading and need to be interpreted based on technological and scientific investigations. The current paper provides an English translation of the two chapters of Bayan al-Sana'at and discusses the less common terms in another section of the paper—"Commentary on the translated chapters". Another section of the paper—"Technical description of methods and materials"—is devoted to the technical contextualisation of the chapters.